(untitled) - Doupnik, Timothy S. (Boston, Mass., 2007)
Doupnik and Perera's International Accounting takes in the whole realm of international accounting, while paying particular focus on the accounting issues related to international business activities and foreign operations.
Keywords: International business enterprises,Sự thanh toán quốc tế; Accounting